It is good to be average: Ecological correlates of breeding phenology in an Arctic seabird, Alle alle (Dovekie) - Ribeiro, Léa; Devogel, Marion; Grissot, Antoine; Kidawa, Dorota; Jakubas, Dariusz; Syposz, Martyna; Wojczulanis-Jakubas, Katarzyna (Zenodo, 2024)
Recognising importance of deviation from a population mean in an animal's behavior is not only necessary to understand the evolution and stability of the whole system but also to predict the future of a population in an altering environment. Arctic seabirds are expected to exhibit high synchronization in timing of breeding at the population level, due to highly seasonal and harsh environmental conditions. Nevertheless, even in such a highly synchronized system, there are always some earlier and later breeders, and what causes this inter-pair variation remains an intriguing question. Using a set of eight years of data on the dovekie ( Alle alle ), a small Arctic seabird, we examined potential drivers of the observed distribution of breeding phenology. We found that dovekie pairs were quite repeatable in their phenology, and preserved their phenological status, with their chicks hatching consistently before, during, or after the population median date for hatching, despite that calendar position of the median shifted between years. This would suggest that the timing of breeding is associated with some pair characteristics, either via properties of the nest or/and some partners traits. However, breeding phenology of the pair was not dependent on nest location, neither pair bond duration nor morphological similarity of the partners. Importantly, timing of breeding was negatively associated with chick growth rate, indicating fitness consequences of phenology. Our simulation further suggests that chance of fledgling survival in the context of predation may be the highest for the chicks that hatched during the peak of hatching period. While our results suggest that the timing of the breeding is important for the reproductive outcome, further research is required to determine the drivers of the repeatability within the dovekie pairs. Funding provided by: National Science Center ROR ID: https://ror.org/03ha2q922 Award Number: 2017/25/B/NZ8/01417 Funding provided by: National Science Center ROR ID: ...